Intervensi Negara Melalui Lembaga Hisbah Untuk Keseimbangan Harga Dalam Perspektif Hukum Ekonomi Syariah - Miftakhul Huda (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2019)
Abstract Indonesia is a country where the majority of the population is Muslim, Islam in intervention activities allows state interference in economic activities. Because, if economic activities only rely on market mechanisms, it can be a fatal risk for general problems. The weakness of the market mechanism is that the market is always in favor of the strong, both in terms of capital, science, technology, and management. In addition, there is interference from the government. The government intervention of the Republic of Indonesia in handling current economic problems is one of them through Law No. 39 of 2007 concerning customs. Illegal export and import goods can damage the economic system because it disrupts the market balance. So the definition of market intervention is government interference in regulating the market economy, which aims to maintain price stability. The main purpose is to control the developing price situation, whether it is normal or there is a price surge, is it due to scarcity of goods or other factors that are not fair. From this inspection, the monitoring team gets objective data that can be followed up in response.